2020
DOI: 10.3390/ijms21207574
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Modulation of Angiogenesis and Immune Response on a Collagen Matrix via Extracorporeal Shockwaves

Abstract: The effective management of tissue integration and immunological responses to transplants decisively co-determines the success of soft and hard tissue reconstruction. The aim of this in vivo study was to evaluate the eligibility of extracorporeal shock wave therapy (ESWT) with respect to its ability to modulate angiogenesis and immune response to a collagen matrix (CM) for tissue engineering in the chorioallantoic membrane (CAM) assay, which is performed with fertilized chicken eggs. CM were placed on the CAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 57 publications
(98 reference statements)
0
17
0
Order By: Relevance
“…Furthermore, possible implications for angiogenesis were analyzed via the CAM assay in vivo. The assay has been well-described for this indication and widely used in the literature [ 7 , 20 ]. As a major advantage, this approach is in accordance with the concept of the replacement of experimental animals, the reduction of the total number of experimental animals needed, and refined testing protocols (“3R aspects”: replacement, reduction, refinement [ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, possible implications for angiogenesis were analyzed via the CAM assay in vivo. The assay has been well-described for this indication and widely used in the literature [ 7 , 20 ]. As a major advantage, this approach is in accordance with the concept of the replacement of experimental animals, the reduction of the total number of experimental animals needed, and refined testing protocols (“3R aspects”: replacement, reduction, refinement [ 30 ]).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it can respond to osteogenic stimuli and offers significant potential as an in vivo model for xenograft organ culture [ 31 , 32 ]. Evidence has shown that the assay may also be used to evaluate possible inflammatory processes and is therefore of great interest for future studies in the field of tissue engineering, especially with platelet-derived concentrates [ 20 , 33 ]. Here, microscopically and immune-histochemically, all tested BSMs led to a noteworthy decrease in vessel-formation and branching-points in comparison to PRF alone.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The number of vessel branches as well as vessel size and vascular density are frequently used as parameters for quantification [34,37,40,41,[43][44][45]. A detailed methodological description of the monitoring of microvessel density as well as vessel branches and junctions was recently published by Heimes et al [88]. Histological and immunohistochemical analysis of the CAM can also be used for the determination of vessel density [42].…”
Section: Methods To Assess Vascularizationmentioning
confidence: 99%
“…Previous studies already proved that the chicken chorioallantoic membrane assay (CAM assay) is well suited for assessing the biocompatibility of nanomaterials [32], their fate within the organism, and hemocompatibility, as well as potential toxic effects [33]. Furthermore, the CAM is an excellent platform with which to study angiogenesis [34] and the angiogenetic activity of biomaterials [35,36].…”
Section: Chicken Chorioallantoic Membrane Assay (Cam-assay)mentioning
confidence: 99%